Deviance-Soc 307 - Barrett, Deborah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course focuses on the various types and causes of deviance, and the interaction (both actions and responses) between those who make society's rules and those who violate them. We begin by defining deviance and examining various traditional and modern theoretical perspectives, as well as how these theories rely on and imply certain methods for studying deviance. We will examine various types of deviant behavior from formal criminal behavior to more informal deviant subcultures. The issue of race, class, gender, historical and cultural contexts relating to deviance will be discussed throughout the course as well.